2017
DOI: 10.1021/acs.jpclett.7b00442
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photodissociation of Selected Gold Clusters: Ultraefficient Unstapling and Ligand Stripping of Au25(pMBA)18 and Au36(pMBA)24

Abstract: We report the first results of ultraviolet photodissociation (UVPD) mass spectrometry of trapped monolayer-protected cluster (MPC) ions generated by electrospray ionization. Gold clusters Au(pMBA) and Au(pMBA) (pMBA = para-mercaptobenzoic acid) were analyzed in both the positive and negative modes. Whereas activation methods including collisional- and electron-based methods produced relatively few fragment ions, even a single ultraviolet pulse (at λ = 193 nm) caused extensive fragmentation of the positively ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
(72 reference statements)
1
32
0
Order By: Relevance
“…For p -MBA, Au 36 (MBA) 24 is also formed and can be isolated during the purification process. 25 Clearly, an isomeric effect of mercaptobenzoic acids on the preparation of Au 25 (MBA) 18 NCs is observed. This may be explained qualitatively based on steric hindrance of the carboxylic group (bulkiness of the carboxylic groups with respect to other benzene rings in the ligand shell, see Scheme 1) and its ion-pairing with tributylamine.…”
Section: Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For p -MBA, Au 36 (MBA) 24 is also formed and can be isolated during the purification process. 25 Clearly, an isomeric effect of mercaptobenzoic acids on the preparation of Au 25 (MBA) 18 NCs is observed. This may be explained qualitatively based on steric hindrance of the carboxylic group (bulkiness of the carboxylic groups with respect to other benzene rings in the ligand shell, see Scheme 1) and its ion-pairing with tributylamine.…”
Section: Results and Discussionmentioning
confidence: 97%
“…CID on gold NCs in mass spectrometers was reported in previous works for different charge states, in both positive and negative modes, and with different ligands. 25,3740 Usually, whatever the ligand, CID experiments lead to dissociation of the protecting ligand staples and formation of ions with higher- m / z ratios. Of note, the nature (protonation, deprotonation, counterion adducts, etc) as well as the number of charges affect the fragmentation pattern; however, the obtained fragments are not sufficient for structural characterization.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example Black et al have recently investigated the use of high energy UV light to efficiently strip ligands from Au 25 (SR) 18 and Au 36 (SR) 24 clusters. 118 Ultraviolet photodissociation mass spectrometry measurements showed that single high energy ultraviolet pulses (l ¼ 193 nm) could cause extensive stripping of ligands off the staple motifs without removing any of the underlying Au atoms, while ve or more pulses resulted in the formation of Au 4 (SR) 4 tetramers and Au atom loss from the clusters. While this essentially is a pure mass spectrometry report, the use of high energy ultraviolet light pulses to remove ligands would be a novel concept towards activating clusters on supports.…”
Section: Discussionmentioning
confidence: 99%
“…While both CID and SID produces a lesser number of fragments, extensive fragmentation can be observed by ultraviolet photodissociation (UVPD) as observed in the case of Au 25 (pMBA) 18 and Au 36 (pMBA) 24 NCs 93 . UVPD on these clusters using λ = 193 nm involved high-energy fragmentation pathways and cleavage of Au-S and C-S bonds.…”
Section: Gas-phase Dissociation Studies Of Noble Metal Nanoclustersmentioning
confidence: 99%